1576 Safeguarding Tools in Paediatric Burns. (12th October 2021) - Dhillon, D; Ibrahim, Y; Vijaysurej, K; Li, Z; Malik, M; Nijran, A; Yarrow, J; Drew, P
Abstract: Introduction: When assessing paediatric patients presenting with burns, non-accidental injury always has to be considered. In our department, local policy dictates that all patients aged 18 or below should have a child safeguarding tool completed on initial clerking. Method: A retrospective audit of all paediatric burns seen over one month was performed. Primary outcome measures included completion of a safeguarding tool and documentation of referral outcome. These results were presented locally and implementing changes were carried out. This was then re-audited over a further monthly period. Results: Initial data collection showed a safeguarding tool completion rate of 69% and referral outcome documentation rate of 50% (n = 16). Implement changes included dissemination of initial audit results to the department, changing the layout of our clerking proformas and introducing posters in the unit which provided more information on risk assessing paediatric patients. The re-audit results showed a safeguarding tool completion rate of 100% and a referral outcome documentation rate of 100% (n = 14). Conclusions: There was a significant improvement in both the safeguarding tool completion and referral outcome documentation rates following our interventions. Simple measures just such education and strategic adjustments of clerking proformas have been shown to be effective measures for increasing documental compliance of child safeguarding tools.